Sosialisasi Bahaya Lingkungan Dan Kesehatan Akibat Penggunaan Plastik Bagi Ibu Rumah Tangga - Tanjung, Revi Maylina; Muharmi, Melvi; Teguh Setyawan; Khoiriyah, Rani; Widya Twiny Rizki; Defia Indah Permatasari; Nur Jaya; Fiqri Al Faruqi; M. Ardi Daya; Elika Fitriani (Jurnal Pengabdian Masyarakat Pinang Masak, 2025)
Plastic is a synthetic polymer material that can be shaped and used in various functions, especially in household products, ranging from plates, glasses, spoons, cooking utensils to food storage containers. According to research, the use of plastic that does not meet the requirements can cause serious health problems such as cancer. Plastic waste is also difficult to decompose or degrade and takes up to hundreds of years to be completely decomposed by soil microorganisms. The purpose of this community service is to provide education to housewives about plastic and the dangers of plastic use for health and the environment. This service was carried out on August 30, 2025 in RT 04 RW 01 Mendalo Indah Village, Jambi Luar Kota District, Muaro Jambi Regency, Jambi Province. The implementation of the socialization was carried out in several stages, namely: 1) Preparation Stage including a pretest to determine the initial level of understanding of participants 2) Implementation Stage including the presentation of materials and distributing brochures to participants 3) Mentoring Stage where participants were given various other alternatives to avoid the use of plastic in everyday life and 4) Success Stage The activity was carried out by analyzing the data processing of the number of answers of each participant to each instrument 'Use of Plastic Packaging Products in Everyday Life'. The aspects of assessing the success of the activity consisted of high, medium and low. The instrument for the level of success of the activity was made with the answer 'yes' or 'no. And after the mentoring process, data on respondents' understanding of the socialization activity was obtained with high success indicator results compared to before the socialization. In conclusion, socialization of the dangers of plastic use is a critical step in minimizing problems with health and environmental pollution. By increasing public awareness, it is hoped that there will be changes in behavior and real actions in reducing the use of single-use plastics and those that do not meet SNI standards.